2022
DOI: 10.1177/15691861221075715
|View full text |Cite
|
Sign up to set email alerts
|

Identifying subgroups based on self-assessment of ability in patients with schizophrenia and its relationship with vocational outcomes

Abstract: Background/Objectives People with schizophrenia have defective self-assessment of ability (i.e., loss of introspective accuracy [IA]). Although previous studies grouped people according to the degree of IA, the clinical features of these subgroups have not been clarified. Additionally, the determinants of outcomes depending on self-assessment remain unknown. We aimed to identify the clinical features that can help distinguish these subgroups and whether the determinants of vocational outcomes differed between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…It is notable that, compared to papers examining cognitive ability, more papers that examined everyday functioning found greater concordance between subjective and objective measures [27,32,35,37]. More concrete skills, such as personal hygiene [26] or employment and daily activities among those currently employed or living independently [29], tended to be estimated more accurately than more abstract skills like interpersonal functioning.…”
Section: Self-reported Everyday Functioning/functional Capacitymentioning
confidence: 95%
See 1 more Smart Citation
“…It is notable that, compared to papers examining cognitive ability, more papers that examined everyday functioning found greater concordance between subjective and objective measures [27,32,35,37]. More concrete skills, such as personal hygiene [26] or employment and daily activities among those currently employed or living independently [29], tended to be estimated more accurately than more abstract skills like interpersonal functioning.…”
Section: Self-reported Everyday Functioning/functional Capacitymentioning
confidence: 95%
“…They found that participants with SSDs reported significantly higher social functioning scores than caregivers and researchers. Okada [37] also looked at social functioning by dividing participants into over-estimation, accurate estimation, and under-estimation groups based on the degree of discrepancy between the SFS and the Life Assessment Scale for Mental Illness. In this study, 31% of participants over-estimated their social functioning, 41% were concordant with informants in their self-estimations, and 28% under-estimated their functioning.…”
Section: Self-reported Everyday Functioning/functional Capacitymentioning
confidence: 99%